2018
DOI: 10.1002/qua.25895
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent QM study on the reaction of HOSO + NO2 with H2O: Nuclear quantum effect on structure and reaction energy profile

Abstract: The hydrogen transfer reaction in the reaction of HOSO + NO2 with and without H2O have been investigated using multicomponent quantum‐mechanics method, which can directly take nuclear quantum effect (NQE) of light nuclei into account. For the case of the reaction without H2O, our calculation reveals that the reaction leading to trans‐HONO is preferred. For the reaction with H2O, water‐non‐mediated and water‐mediated (hydrogen‐relay) hydrogen transfer mechanism are investigated. The NQE of hydrogen nucleus lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Since its first experimental identification in 1996 by Frank et al, the molecular properties and reactivity of the hydroxysulfinyl radical (HOSO) have been extensively studied to understand its role as a key intermediate in sulfur-related processes such as the catalytic removal of chain-propagating radicals , or the formation of sulfur dioxide (SO 2 ) in hot molecular cores . This radical has also gained increasing attention over the past few years because of its potential role in atmospheric chemistry. ,, , HOSO can be generated from SO 2 upon excitation at 250−340 nm, followed by the population of its lowest excited triplet state via intersystem crossing (). , This highly reactive 3 SO 2 species can abstract a H atom from water in the gas phase (), yielding HOSO and a OH radical, in a process favored by partial water solvation in the air–water interface. , …”
mentioning
confidence: 99%
“…Since its first experimental identification in 1996 by Frank et al, the molecular properties and reactivity of the hydroxysulfinyl radical (HOSO) have been extensively studied to understand its role as a key intermediate in sulfur-related processes such as the catalytic removal of chain-propagating radicals , or the formation of sulfur dioxide (SO 2 ) in hot molecular cores . This radical has also gained increasing attention over the past few years because of its potential role in atmospheric chemistry. ,, , HOSO can be generated from SO 2 upon excitation at 250−340 nm, followed by the population of its lowest excited triplet state via intersystem crossing (). , This highly reactive 3 SO 2 species can abstract a H atom from water in the gas phase (), yielding HOSO and a OH radical, in a process favored by partial water solvation in the air–water interface. , …”
mentioning
confidence: 99%
“…[11][12][13] The importance of HOSO comes from its ambient reactivity towards various oxidizing agents present in the atmosphere. In the last few years, there are a few studies [14][15][16][17][18][19][20] on the oxidation of HOSO by various oxidizing agents like H, OH , Cl , NO 2 , NH 2 , etc., where SO 2 is obtained as a final product. The aim of the present work is to study the reaction of HOSO with O 2 ( 3 S g À ) and assess its potential impact on the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…11–13 The importance of HOSO˙ comes from its ambient reactivity towards various oxidizing agents present in the atmosphere. In the last few years, there are a few studies 14–20 on the oxidation of HOSO˙ by various oxidizing agents like H, OH˙, Cl˙, NO 2 , NH 2 ˙, etc. , where SO 2 is obtained as a final product.…”
Section: Introductionmentioning
confidence: 99%
“…Further work has confirmed that the reaction mechanism involves a proton-coupled electron-transfer mechanism that is favored by water solvation, so the activation free energy at the air–water interface is predicted to be low (<1 kcal·mol –1 at 298 K) and the triplet is predicted to be rapidly hydrolyzed . The atmospheric chemistry of HOSO is poorly known, though some studies in the gas phase have been reported. ,, …”
mentioning
confidence: 99%